Influence of base material properties on copper and aluminium-copper explosive welds - Carvalho, Gustavo (2018)
The influence of base material properties on the interfacial phenomena in copper and aluminium-copper explosive welds was studied. Two explosive mixtures with different detonation velocities were tested. Sound aluminium-copper joints with effective bonding were achieved by using an explosive mixture with a lower detonation velocity. High energy explosives led to extensive interfacial melting, preventing the production of consistent dissimilar welds. Unlike to the similar copper joints, the aluminium-copper welds presented very asymmetrical interfacial waves, rich in intermetallic phases and displaying a curled morphology. The interaction of the materials in dissimilar welding was found to be completely different depending on the positioning of each alloy in the joint, i.e. positioned as the flyer or as the baseplate.